Superior prognostic value of right ventricular free wall compared to global longitudinal strain in patients with repaired tetralogy of Fallot - Gao, Ying; Li, He; He, Lin; Zhang, Yanting; Sun, Wei; Li, Meng; Gao, Lang; Lin, Yixia; Ji, Mengmeng; Lv, Qing; Wang, Jing; Zhang, Li; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives Both right ventricular free wall longitudinal strain (RVFWLS) and right ventricular global longitudinal strain (RVGLS) using two-dimensional speckle tracking echocardiography (2D-STE) has been demonstrated to predict adverse outcomes in patients with repaired tetralogy of Fallot (r-TOF). However, RVGLS may be affected by left ventricular (LV) function owing to the fact that the interventricular septum is also a part of the left ventricle. Therefore, the aim of our study was to compare the predictive value of RVFWLS with that of RVGLS in patients with r-TOF. Materials and methods A total of 179 patients with r-TOF were included in this study. RVFWLS, RVGLS, and left ventricle global longitudinal strain (LVGLS) were evaluated by 2D-STE. The adverse clinical events were death or r-TOF-related rehospitalization. Prognostic performance was evaluated by C-statistic and Akaike information criterion (AIC). Results Thirty-one patients developed poor outcomes during a median follow-up period of 2.8 years. Compared with patients without end-point events, those with end-point events had higher incidence of moderate/severe pulmonary regurgitation, larger right heart sizes, and lower RV fractional area change (RVFAC), RVFWLS, RVGLS, and LVGLS than those without. Multivariate Cox regression analysis revealed that RVFAC, RVFWLS, RVGLS, and LVGLS were predictive of poor outcomes in patients with r-TOF after adjustment for transannular patch and QRS duration. A Cox model using RVFWLS (C index = 0.876, AIC = 228) was found to predict unfavorable outcomes more accurately than a model with RVGLS (C index = 0.856, AIC = 243), RVFAC (C index = 0.811, AIC = 248), and LVGLS (C index = 0.830, AIC = 248). Conclusion Although both RVGLS and RVFWLS are associated with adverse events, RVFWLS provides superior prognostic value than that of RVGLS in patients with r-TOF.